Altman Z-Score dan Grover G-Score Dalam Analisis Kebangkrutan PT. Sepatu Bata Tbk Periode Tahun 2014 - 2020 - Joselina Tuhuteru (Univiversitas Dr. Djar Wattiheluw, 2022)
During the COVID-19 pandemic in Indonesia, PT. Sepatu Bata Tbk recorded a net loss in 2020 of IDR 177,761,030,000 down 858% from the previous year. The company’s financial statements reflect the company’s performance. If there is a continuous decline in profits, it is possible that the company will go bankrupt. The purpose of this study was to predict the risk of corporate bankruptcy at PT. Sepatu Bata, Tbk so that companies can anticipate, prevent and reduce the risk of bankruptcy. This study uses the Altman Z-Score and Grover G-Score methods as a company bankruptcy tool analysis with indicators for the company’s financial statements for the period of 2014 to 2020. Based on the results of the analysis using the Altman and Grover Methods, in 2020 PT. Sepatu Bata Tbk is estimated to go bankrupt with a Z-Score 0f 0,000 < 1,080 and a G-Score of -0,669 ≤ -0,02